Method for preparing low aspect ratio iron oxide yellow by using surface characteristic adsorption
The surface electrical properties of iron oxide particles are changed through the characteristic adsorption force of inorganic anions, and the problem of anti-fluidity of iron oxide yellow particles is solved, particle size control and viscosity reduction are achieved, the production process is simplified, and the iron oxide yellow pigment is broadened. Industry applications.
Patent Information
- Application Number
- CN202211454863.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-21
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2042-11-21
AI Technical Summary
The high fluid resistance of iron oxide yellow particles makes it difficult to disperse and wet in the coating system, limiting their application in the coating industry. The existing modification methods have problems such as complex production processes, unevenness and agglomeration.
By using the characteristic adsorption force of inorganic anions (such as Cl-, Br-, I-, S2-, F-) on the surface of iron oxide particles, the electrical structure of the surface of particles is changed, and the particle size control is achieved and the aspect ratio is reduced. This improves the fluidity of the pigment.
Effectively reduce the aspect ratio of the iron oxide yellow particles to below 1:5, reduce product viscosity, avoid agglomeration, and simplify the production process, avoiding the addition of organic chemicals.
Smart Images

Figure CN115974164B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing low aspect ratio iron oxide yellow by utilizing surface characteristic adsorption Background Art
[0002] Yellow iron oxide, also known as iron oxide hydroxide, has a chemical formula of α-FeOOH or α-Fe2O3·H2O. Due to its excellent performance, it is widely used in building materials, coatings, paints, plastics and other fields. However, due to the needle-shaped shape of yellow iron oxide particles, its anti-flowability is stronger than other types of equiaxed iron oxides. Therefore, yellow iron oxide shows an inherent high viscosity in most coating systems, making it difficult to disperse and wet well in the medium used, limiting its further application. Therefore, in order to expand the application of yellow iron oxide pigment in the coating industry, it is necessary to improve the shape of yellow iron oxide pigment particles so that it can achieve better flow effect in the coating medium and play a good role.
[0003] At present, both at home and abroad, organic modifiers are usually added to change the surface charge of particles, thereby controlling the shape of pigment particles. The modification mechanism is based on the charge on the surface of the particles, and anionic or cationic surfactants or organic modifiers such as polyelectrolytes are selected to achieve the purpose of surface modification through the electrostatic interaction between the two, thereby improving the viscosity of the pigment. However, this method has problems such as complex production process, uneven surface treatment and easy agglomeration. The literature [Research on Modification Technology and Application of Industrial Inorganic Pigments, Wuhan University of Technology, 2010] describes this in detail.
[0004] Invention patent 201410767118.7 provides a preparation process for low-viscosity yellow iron oxide pigment. This technology destroys the shape of some yellow iron oxide pigment particles by grinding with steel balls, but cannot reduce the aspect ratio of all yellow iron oxide particles as a whole, and its effect is not significant enough. Invention patent 202210427739.5 uses a hydrothermal synthesis method, and adds a surfactant hexadecyltrimethylammonium bromide (CTAB) during the preparation process to change the surface charge of the yellow iron oxide particles to achieve the purpose of controlling the particle size. However, this method is carried out in a high-pressure reactor, and the synthesis conditions are relatively harsh.
[0005] Some electrolytes contain Cl - Br - 、F - ,I - , S 2-In addition to electrostatic forces, there may also be some characteristic adsorption forces between inorganic anions and the surface charges of oxide particles. For inorganic anions, characteristic adsorption forces may include chemical bonding forces, hydrogen bonding forces, and solvation forces. Since the intensity of the interaction between ions with characteristic adsorption forces and the surface of oxide particles is much greater than the electrostatic adsorption force, the water molecules in the hydration shells around the ions and on the surface of the mineral particles may be squeezed out, allowing the ions to be directly and tightly adsorbed on the surface of the particles, changing the potential to determine the ions, thereby changing the charge on the surface of the particles. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a low aspect ratio iron oxide yellow pigment by utilizing the special adsorption performance of inorganic anions in an electrolyte on the surface of iron oxide particles to change the electrical properties of the particle surface. The method can effectively control the particle size of the product and effectively reduce the aspect ratio of the iron oxide yellow particles from 1:11 to below 1:5.
[0007] The specific steps for preparing low aspect ratio iron oxide yellow by surface property adsorption are as follows:
[0008] 1) Seed preparation
[0009] A. Raw material preparation: Add ferrous sulfate solution with a concentration of 1.2 mol / L to 1.7 mol / L into a stainless steel reaction tank; weigh a certain amount of electrolyte and disperse it in deionized water, and stir at room temperature to prepare a salt solution, where [A n- ]=0.002mol / L~0.2mol / L; weigh a certain amount of alkaline reagent and dilute it with deionized water to form an alkaline solution of the same volume, so that the ratio of the amount of the alkaline reagent to the amount of ferrous sulfate is 0.4; add the two solutions into the reaction barrel at the same time, and control the reaction temperature to be 25~35℃;
[0010] B: Air volume control: The total reaction time of the seed preparation process is controlled to be 12 to 17 hours, and the air volume is controlled at 200m 3 / h~600m 3 / h; the final reaction material is stored separately as seed crystals.
[0011] 2) Oxidation reaction
[0012] A: Put a certain amount of iron sheet into the reaction barrel, put the prepared seed crystals into the reaction barrel, and then add the same volume of deionized water to dilute;
[0013] B: Air is introduced into the reaction tank from the bottom, and the steam valve is opened to increase the temperature. The oxidation reaction temperature is controlled at 80±2℃, and the air volume is controlled at 200m 3 / h~600m 3 / h;
[0014] C: When the reaction time reaches 20 to 35 hours and the color of the liquid in the barrel is close to that of the standard sample, start scraping the sample for testing. When the color is similar to that of the standard sample, close the air and steam valves and prepare to release the barrel.
[0015] 3) Post-processing
[0016] A: After the oxidation reaction is completed, open the valve of the reaction tank, release the liquid, filter, rinse, dry and ultra-finely grind the liquid to obtain the finished product.
[0017] In some embodiments, the electrolyte salt solution is one or two of sodium bromide, potassium chloride, ammonium chloride, potassium iodide, potassium bromide, sodium sulfide, sodium fluoride, ammonium fluoride, ammonium sulfide, and lithium chloride.
[0018] In some embodiments, A n- Cl - Br - ,I - , S 2- 、F - One or both of the following.
[0019] In some embodiments, the alkaline solution is sodium hydroxide, sodium carbonate, magnesium carbonate, magnesium hydroxide, calcium hydroxide or aqueous ammonia.
[0020] The surface properties of oxides in aqueous solution and the mechanism of surface charge can be qualitatively obtained through two stages, namely surface hydration plus dissociation of surface hydroxides. The hydration stage can be imagined as the iron oxide using the atoms exposed on the surface to form its nearest coordination layer, and the exposed cation pulls an OH - ions or water molecules to complete the coordination, while H + The final result is that the cation is buried below the surface and the iron oxide surface is covered with hydroxyl groups.
[0021] Oxide particles suspended in aqueous solution tend to be polarized and charged, which is related to the type of charge and the pH of the solution surrounding the particles. The polarization equation under acidic or alkaline conditions can be schematically written as:
[0022]
[0023]
[0024] Where Sur-OH represents the adsorption center on the particle surface. Therefore, H + and OH - Ions are the surface potential determining ions of oxide particles, which determine the isoelectric point of oxide particles.
[0025] In fact, when an oxide is in contact with a solution, when the pH value of the solution is less than its isoelectric point, the oxide tends to be positively polarized and surrounded by compensating anions. If the same oxide is placed in a solution with a pH value higher than its isoelectric point, it tends to be negatively polarized and surrounded by compensating cations.
[0026] The usual modification is to adjust the pH value of the system to be higher than the isoelectric point so that the surface of the iron oxide particles has a negative charge, and then add a cationic organic modifier so that the modifier molecules squeeze into the Stern layer under the electrostatic attraction and intermolecular forces (i.e., electrical attraction), and undergo physical and chemical adsorption on the particle surface, ultimately achieving the degree to which the particle surface is completely covered by the modifier molecules, achieving a good modification effect, and ultimately achieving the purpose of controlling the particle shape and improving other physical and chemical properties.
[0027] The present invention is characterized in that by adding Cl - Br - ,I - , S 2- 、F - The role of the neutral electrolyte of anions is to utilize the special adsorption properties of these inorganic anions on the surface of iron oxide particles. In the process, the inorganic anions are tightly adsorbed on the inner layer of the electric double layer through characteristic adsorption forces (in addition to electrostatic forces, they may also include non-electrical characteristic attractive forces such as chemical bonding forces, hydrogen bonding forces, and solvation forces), changing the potential-determining ions, and then changing the surface interface structure and potential distribution, that is, the purpose of controlling the particle size is achieved by changing the surface charge of the particles.
[0028] On the basis of ensuring production costs, this method can not only effectively control the aspect ratio of pigment particles, produce smaller α-FeOOH seed particles, and reduce product viscosity, but also effectively prevent particle agglomeration. More importantly, this method does not add any organic chemicals during the operation process, and the equipment is extensive, simple, and easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a SEM image of the yellow iron oxide particles in Example 1.
[0030] Figure 2 This is a SEM image of the yellow iron oxide particles in Example 2.
[0031] Figure 3 This is a SEM image of the yellow iron oxide particles in Example 3. DETAILED DESCRIPTION
[0032] Example 1
[0033] 1) Seed preparation
[0034] A. Raw material preparation: add 1L of 1.2mol / L ferrous sulfate heptahydrate solution into a stainless steel reaction barrel; weigh 0.013mol potassium bromide and disperse it in 100mL deionized water, and stir at room temperature to prepare a salt solution; measure 7.4mL of ammonia water and use deionized water to prepare an alkaline solution of the same volume, so that the ratio of the amount of the alkaline agent to the amount of ferrous sulfate is 0.4; add these two solutions into the reaction barrel at the same time, and control the reaction temperature to be 25-35°C;
[0035] B: Air volume control: The total reaction time of the seed preparation process is controlled to be 12 to 17 hours, and the air volume is controlled at 200m 3 / h~600m 3 / h; the final reaction material is stored separately as seed crystals.
[0036] 2) Oxidation reaction
[0037] A: Put a certain amount of iron sheet into the reaction barrel, put the prepared seed crystals into the reaction barrel, and then add the same volume of deionized water to dilute;
[0038] B: Air is introduced into the reaction tank from the bottom, and the steam valve is opened to increase the temperature. The oxidation reaction temperature is controlled at 80±2℃, and the air volume is controlled at 200m 3 / h~600m 3 / h;
[0039] C: When the reaction time reaches 20 to 35 hours and the color of the liquid in the barrel is close to that of the standard sample, start scraping the sample for testing. When the color is similar to that of the standard sample, close the air and steam valves and prepare to release the barrel.
[0040] 3) Post-processing
[0041] A: After the oxidation reaction is completed, open the valve of the reaction tank, release the liquid, filter, rinse, dry and ultra-finely grind the liquid to obtain the finished product.
[0042] Example 2
[0043] 1) Seed preparation
[0044] A. Raw material preparation: add 1L of 1.2mol / L ferrous sulfate heptahydrate solution into a stainless steel reaction barrel; weigh 0.013mol lithium chloride and disperse it in 100mL deionized water, and stir at room temperature to prepare a salt solution; weigh 5.09g sodium carbonate and prepare an alkaline solution of the same volume with deionized water, so that the ratio of the amount of the alkaline agent to the amount of ferrous sulfate is 0.4; add these two solutions into the reaction barrel at the same time, and control the reaction temperature to be 25-35°C;
[0045] B: Air volume control: The total reaction time of the seed preparation process is controlled to be 12 to 17 hours, and the air volume is controlled at 200m 3 / h~600m 3 / h; the final reaction material is stored separately as seed crystals.
[0046] 2) Oxidation reaction
[0047] A: Put a certain amount of iron sheet into the reaction barrel, put the prepared seed crystals into the reaction barrel, and then add the same volume of deionized water to dilute;
[0048] B: Air is introduced into the reaction tank from the bottom, and the steam valve is opened to increase the temperature. The oxidation reaction temperature is controlled at 80±2℃, and the air volume is controlled at 200m 3 / h~600m 3 / h;
[0049] C: When the reaction time reaches 20 to 35 hours and the color of the liquid in the barrel is close to that of the standard sample, start scraping the sample for testing. When the color is similar to that of the standard sample, close the air and steam valves and prepare to release the barrel.
[0050] 3) Post-processing
[0051] A: After the oxidation reaction is completed, open the valve of the reaction tank, release the liquid, filter, rinse, dry and ultra-finely grind the liquid to obtain the finished product.
[0052] Example 3
[0053] 1) Seed preparation
[0054] A. Raw material preparation: add 1L of 1.2mol / L ferrous sulfate heptahydrate solution into a stainless steel reaction barrel; weigh 0.013mol sodium fluoride and disperse it in 100mL deionized water, and stir at room temperature to prepare a salt solution; weigh 1.92g of sodium hydroxide and use deionized water to prepare an alkaline solution of the same volume, so that the ratio of the amount of the alkaline agent to the amount of ferrous sulfate is 0.4; add these two solutions into the reaction barrel at the same time, and control the reaction temperature to be 25-35°C;
[0055] B: Air volume control: The total reaction time of the seed preparation process is controlled to be 12 to 17 hours, and the air volume is controlled at 200m 3 / h~600m 3 / h; the final reaction material is stored separately as seed crystals.
[0056] 2) Oxidation reaction
[0057] A: Put a certain amount of iron sheet into the reaction barrel, put the prepared seed crystals into the reaction barrel, and then add the same volume of deionized water to dilute;
[0058] B: Air is introduced into the reaction tank from the bottom, and the steam valve is opened to increase the temperature. The oxidation reaction temperature is controlled at 80±2℃, and the air volume is controlled at 200m 3 / h~600m 3 / h;
[0059] C: When the reaction time reaches 20 to 35 hours and the color of the liquid in the barrel is close to that of the standard sample, start scraping the sample for testing. When the color is similar to that of the standard sample, close the air and steam valves and prepare to release the barrel.
[0060] 3) Post-processing
[0061] A: After the oxidation reaction is completed, open the valve of the reaction tank, release the liquid, filter, rinse, dry and ultra-finely grind the liquid to obtain the finished product.
[0062] The iron yellow seed particles obtained from the three groups of experiments in Examples 1-3 were characterized using a SU8010 scanning electron microscope. Figure 1-3 shown.
[0063] The viscosity of the paint paste with the same solid content was measured using a Stormer viscometer. The viscosity values of the experimental products were measured while ensuring that the solid content of the paint pastes measured was the same, as shown in Table 1 below:
[0064] Finished Product Aspect Ratio Viscosity Ordinary process 1:11 120KU Example 1 1:8 75KU Example 2 1:7 59KU Example 3 1:4 36KU
[0065] Through three sets of experiments, it can be clearly seen that the anion Cl in the inorganic electrolyte - Br - ,I - , S 2- 、F - Due to the characteristic adsorption on the surface of iron oxide particles, the aspect ratio of the iron oxide yellow pigment particles is effectively reduced, and as the aspect ratio of the iron oxide yellow particles decreases, its corresponding viscosity also decreases.
[0066] In the present invention, the experimental conditions of the examples cited are not limited to this. The numerical values exemplified above are reference values in the experimental process and are only preferred embodiments of the present invention and are not used to limit the present invention. All modifications, replacements and improvements made based on the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing low aspect ratio iron oxide yellow, characterized in that: The method comprises the following steps: 1) Seed preparation: A. Raw material preparation: Add 1.2mol / L~1.7mol / L ferrous sulfate solution into a stainless steel reaction tank; weigh a certain amount of electrolyte and disperse it in deionized water, stir at room temperature to prepare a salt solution, where the anion [A n- ]=0.002mol / L~0.2mol / L; weigh a certain amount of alkaline reagent and use deionized water to prepare an alkaline solution of the same volume, so that the ratio of the amount of the alkaline reagent to the amount of ferrous sulfate is 0.4, and the two solutions are added to the reaction barrel at the same time, and the reaction temperature is controlled to be 25-35°C; the salt solution is one or two of sodium bromide, potassium chloride, ammonium chloride, potassium iodide, potassium bromide, sodium sulfide, sodium fluoride, ammonium fluoride, ammonium sulfide, and lithium chloride, [A n- ]=0.002mol / L~0.2mol / L, A n- Cl - Br - ,I - , S 2- 、F - One or two of the following: the alkaline solution is sodium hydroxide, sodium carbonate, magnesium carbonate, magnesium hydroxide, calcium hydroxide or ammonia water; B: Air volume control: The total reaction time of the seed preparation process is controlled to be 12-17h, and the air volume is controlled at 200m 3 / h~600 m 3 / h; the final reaction material is stored separately as seed crystals; 2) Oxidation reaction: A: Put a certain amount of iron sheet into the reaction barrel, put the seed crystals prepared in step 1) into the reaction barrel, and then add the same volume of deionized water to dilute; B: Air is introduced into the reaction tank from the bottom, and the steam valve is opened to increase the temperature. The oxidation reaction temperature is controlled at 80±2℃, and the air volume is controlled at 200m 3 / h~600m 3 / h; C: When the reaction time reaches 20-35 hours, observe that the color of the liquid in the barrel is close to that of the standard sample, start the scraping test, and when the color is close to that of the standard sample, close the air and steam valves and prepare to release the barrel; 3) Post-processing: A: After the oxidation reaction is completed, open the valve of the reaction tank, release the liquid, filter, rinse, dry and ultra-finely grind the liquid to obtain the finished product.